Cervical cancer burden among females under 40 years in China, Japan, and South Korea, 1990–2021: a systematic analysis for the global burden of disease study 2021 - Xiao, Caiyan; Deng, Juan; Ren, Fangyuan; Zhang, Chan (Frontiers in Public Health, 2025)
BackgroundCervical cancer remains a major global public health concern; however, its burden among younger women in East Asia has not been systematically characterized across spatial, temporal, and age dimensions.MethodsThis study analyzed the incidence, prevalence, mortality, and DALYs of cervical cancer among females aged <40 years in China, Japan, and South Korea from 1990 to 2021 using GBD 2021 data. The results highlight distinct geographic and temporal patterns with urgent implications for public health policies. Strengthening HPV vaccination, expanding screening, and targeted campaigns are critical to reducing the burden and aligning with the WHO elimination goals.ResultsBetween 1990 and 2021, the burden of cervical cancer among females aged <40 years in China, Japan, and South Korea showed distinct geographic and temporal patterns. In 2021, Japan maintained the highest incidence, prevalence, and DALYs, whereas China recorded the highest mortality. Temporal trends indicated a rising incidence in Japan and China but a decline in South Korea, while mortality and DALY rates decreased substantially in China and South Korea and remained low in Japan. Across all countries, the burden was predominantly concentrated in women aged 30–39 years, with a stable overall age composition, but a slight increase in the proportion of the 35–39-year group over time.ConclusionDespite modest reductions in age-standardized burden, cervical cancer remains a significant issue for women under 40 years of age in East Asia, compounded by suboptimal HPV vaccine uptake and COVID-era disruptions. Therefore, strengthening vaccination, expanding screening, and launching public health campaigns are urgent priorities.